Residue Levels And Human Health Risk Assessment Of Heavy Metals In Commercial Fish And Shrimp Species From Calabar, Nigeria. - OYO-ITA, I. O.; NKOM, P. Y.; UMO, F. E.; ETON, E.; NEJI, H. A.; OYO-ITA, O. E. (European Journal of Applied Sciences, 2022)
Selected heavy metals accumulation and health risk assessment were investigated in the tissues of the widely consumed fish (Ethmalosa Fimbriata, Clarias Gariepenus, and Tilapia Guineensis) and shrimp (Macrobrachium Felicinum) species in Calabar. The mean concentrations of Cr, Pb, and Ni were slightly higher than the standard levels and Hg was below detection level for all samples. Zn, Cd and Cu contents of fish and shrimp were below the maximum guideline proposed by the US Food and Drug Administration. The average estimated weekly intake was significantly below the provisional tolerable intake based on the FAO and WHO standards for all studied metals. The combined Total hazard quotient (THQ) of the studied heavy metals were above 1 that is 7.48 for the fish and 7.0 for the shrimp and was highest for Cr suggesting a possible carcinogenic risk to consumers of this product via Cr. The carcinogenic risk of Pb in both species was within the acceptable range of 10-4 -10-6 mg/kg/day. Results of this study reveal an almost safe level of Zn, Cd, Cu, and Hg contents in the fish and shrimp consumed by Crossrivarians but recommend to appropriate authorities to stop the sources and use of Cr, Pb, and Ni.